Post vitrification survivability of 2-cell stage IVP buffalo embryos: effect of concentration - Kumar, Suresh; Jhamb, Dinesh; Maurya, S N (The Indian Journal of Animal Sciences, 2011)
Good quality cumulus oocyte complex (COCs) aspirated from follicles>2 mm in abattoir buffalo ovaries were cultured in TCM-199 with 10% FCS, hormones, and antibiotics in 5% CO2; 95% humidity at 38.5°C for 24–26 h for in vitro maturation (IVM). In vitro capacitation of bubaline spermatozoa was achieved using heparin. In vitro matured oocytes and in vitro capacitated spermatozoa were coincubated in pre-equilibrated fertilization drops for in-vitro fertilization (IVF) and further cultured for cleavage and 2-cell in-vitro produced bubaline embryos were obtained, which were used for cryopresevation by vitrification. The 2-cell stage embryos were exposed to different mole concentrations (0–4 M) of dimethyl sulphoxide (DMSO) or 1, 2- propanediol (PROH) or the combination of DMSO and PROH in serially ascending concentrations grouped at 0.5 M interval along with 0.25 M sucrose with 2 min equilibration at each step. The embryos were vitrified and stored in liquid nitrogen for 7 or more days and then warmed and cryoprotectants were removed by placement of embryos in medium with serially descending concentrations of the cryoprotectants containing 0.5 M sucrose. The embryos were co-cultured with oviductal cells in TCM -199. The post vitrification developmental competence or cleaving ability was used for assessing suitability of the concentration of cryoprotectants. The results indicated that 1.5 M DMSO provided best cryoprotection (35.71%) to 2-cell stage buffalo embryos, whereas PROH performed better at 2.0 M (30.76%). When a combination of PROH and DMSO (1:1) was used the optimum concentration was found to be 1.0 M (33.33%).